2019
DOI: 10.1155/2019/4684815
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Real-Time and Retrospective Continuous Glucose Monitoring in Patients with Type 2 Diabetes Mellitus: A Meta-Analysis of Randomized Controlled Trials

Abstract: In the present study, we aimed to investigate the effects of continuous glucose monitoring (CGM) on blood glucose levels, body weight, blood pressure, and hypoglycaemia in patients with type 2 diabetes mellitus using a meta-analysis of randomized controlled trials (RCTs). A literature search was performed using MEDLINE, Cochrane Controlled Trials Registry, and ClinicalTrials.gov. RCTs using CGM in patients with type 2 diabetes mellitus were then selected. Statistical analysis included calculation of the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 34 publications
8
50
1
5
Order By: Relevance
“…The results of the present study are similar to those of a recent meta‐analysis which also included restrospective CGM and observational studies . Conversely, a meta‐analysis that only included randomized trials estimated an effect of real‐time CGM on HbA1c greater than that assessed in the present analysis; however, this latter analysis included one trial in which CGM was used intermittently for a short time, and it did not include another trial that was published after the end of the study search . Available data are insufficient, however, to draw clear conclusions on the effect of CGM on hypoglycaemic risk and on quality of life; notably, no increase in hypoglycaemic risk was observed despite a reduction in HbA1c.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results of the present study are similar to those of a recent meta‐analysis which also included restrospective CGM and observational studies . Conversely, a meta‐analysis that only included randomized trials estimated an effect of real‐time CGM on HbA1c greater than that assessed in the present analysis; however, this latter analysis included one trial in which CGM was used intermittently for a short time, and it did not include another trial that was published after the end of the study search . Available data are insufficient, however, to draw clear conclusions on the effect of CGM on hypoglycaemic risk and on quality of life; notably, no increase in hypoglycaemic risk was observed despite a reduction in HbA1c.…”
Section: Discussionsupporting
confidence: 71%
“…A recent meta‐analysis of patient‐level data from controlled trials on CSII, as compared to MDI, in type 2 diabetes showed a small but statistically significant reduction in HbA1c . Two further meta‐analyses of study‐level data showed a more relevant effect of real‐time CGM on glycaemic control in people with type 2 diabetes, in comparison with traditional self‐monitoring of blood glucose (SMBG); however, one of those two meta‐analyses also included observational studies, and both considered retrospective CGM, together with real‐time CGM.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies will want to confirm that better workup and diagnosis resulted in better glucose control, although there already is substantial evidence that this is the case in other settings. 17,18 Another limitation is that this study did not look at specialist referrals. We recognize that an alternative to the PCP changing the therapy would be to send the patient to a diabetes specialist.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has only searched three databases so that it may not include all relevant studies. Besides, it did not compare different types of CGM devices [16].…”
Section: Introductionmentioning
confidence: 99%